2001
DOI: 10.1093/ndt/16.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of dialysis reduces the doses of recombinant erythropoietin independently from the use of biocompatible membranes in haemodialysis patients

Abstract: In iron-replete HD patients treated with rHuEpo in the maintenance phase, Kt/V exerts a significant sparing effect on rHuEpo requirement independent of the use of biocompatible synthetic membranes. By optimizing rHuEpo responsiveness, an adequate dialysis treatment can contribute to the reduction of the costs of rHuEpo therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
5
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 17 publications
7
45
5
3
Order By: Relevance
“…18 In a study involving 68 patients, Movilli and colleagues emphasize that adequate dialysis in iron-replete patients contributes to optimize rhEPO responsiveness independent of the use of biocompatible synthetic membranes. 19 The results of the present study are in agreement with these statements: no difference in Hgb and DA dose could be found using 3 different membranes (the number of patients using polyacrylonitrile is too small). We observed that, with an adequate dialysis ensuring stable biological parameters, the use of 3 different membranes and different times of injections during the HD session did not result in a clinical difference in the management of anemia with DA.…”
Section: Discussionsupporting
confidence: 91%
“…18 In a study involving 68 patients, Movilli and colleagues emphasize that adequate dialysis in iron-replete patients contributes to optimize rhEPO responsiveness independent of the use of biocompatible synthetic membranes. 19 The results of the present study are in agreement with these statements: no difference in Hgb and DA dose could be found using 3 different membranes (the number of patients using polyacrylonitrile is too small). We observed that, with an adequate dialysis ensuring stable biological parameters, the use of 3 different membranes and different times of injections during the HD session did not result in a clinical difference in the management of anemia with DA.…”
Section: Discussionsupporting
confidence: 91%
“…Kt, the top part of the fraction, is clearance multiplied by time, representing the volume of fluid completely cleared of urea during a single treatment V, the bottom part of the fraction, is the volume of water a patient's body contains. Many studies confirmed the idea of association of well removal of uremic inhibitors of erythropoiesis through adequate dialysis dose and getting the target responsiveness to the Epo treatment suggesting that the more inflamed patients could have a lower Kt/V because of difficulties in performing HD [47,48]. However, our finding in the studied patients was that increased dialysis dose (Kt/V) is associated with higher ERI.…”
Section: Individual Response Variations To Erythropoietin Stimulatingsupporting
confidence: 69%
“…The physiologic mechanism through which the erythropoietic response is compromised at high ferritin levels could be explained by the malnutrition-inflammation complex syndrome inhibiting the erythropoiesis (28). A link between the dialysis adequacy and the erythropoietic response has been established before (14,15,29). Our results confirm the finding by Movilli et al (29), who established a negative correlation between the total Epo dose and Kt/V when Kt/V is below 1.33 and no correlation when it is above 1.33.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, iron stores are most thoroughly described (7)(8)(9)(10)(11). Other factors include inflammation (12,13), adequacy of dialysis (14,15), nutritional status (16), and hyperparathyroidism (17).…”
mentioning
confidence: 99%